2013
DOI: 10.1007/s00280-013-2078-0
|View full text |Cite
|
Sign up to set email alerts
|

An integrin-targeted, pan-isoform, phosphoinositide-3 kinase inhibitor, SF1126, has activity against multiple myeloma in vivo

Abstract: Purpose Multiple reports point to an important role for the phosphoinositide-3 kinase (PI3K) and AKT signaling pathways in tumor survival and chemoresistance in multiple myeloma (MM). The goals of our study were: (1) to generate the preclinical results necessary to justify a Phase I clinical trial of SF1126 in hematopoietic malignancies including multiple myeloma, and (2) to begin combining pan PI-3 kinase inhibitors with other agents to augment antitumor activity of this class of agent in preparation for comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…Our drug simulation indicated that combination of PI3K and integrin inhibitors potentially reduced the myeloma cell proliferation in normoxia and inhibited cell migration in hypoxia. These predicted results were consistent with the previously reported results 40 41 .…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…Our drug simulation indicated that combination of PI3K and integrin inhibitors potentially reduced the myeloma cell proliferation in normoxia and inhibited cell migration in hypoxia. These predicted results were consistent with the previously reported results 40 41 .…”
Section: Resultssupporting
confidence: 94%
“…The combination of these two therapeutic agents has improved outcomes for MM patients 41 . SF1126 , an integrin-targeted PI3K inhibitor, has potent antitumor activity against multiple myeloma in vitro and in vivo 40 . Treatment with SF1126 on MM appeared to affect the tumor microenvironment by inhibiting angiogenesis 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Cells were harvested at 72 hours. Beta-catenin, PTEN, pGSK3β, GSK-3β and MMP7 protein levels were determination of by Western blot [32]. …”
Section: Methodsmentioning
confidence: 99%
“…However, genetic lesions that directly affect genes for PI3K isoforms do not occur in MM (Müller et al , ; Ismail et al , ; Chapman et al , ; Leich et al , ), although oncogenic signalling via the PI3K/Akt axis is a prominent feature in MM cells (Hsu et al , ; Zöllinger et al , ; Baumann et al , ; Steinbrunn et al , ; Ramakrishnan et al , ; Munugalavadla et al , ). Inhibition of PI3K activity may therefore represent a promising therapeutic strategy to target the disease in a large subgroup of MM patients, and we and others have previously demonstrated that abrogation of PI3K‐dependent signalling impairs MM cell survival (Hsu et al , ; Pene et al , ; Zöllinger et al , ; Steinbrunn et al , , ; Stengel et al , ; De et al , ; Azab et al , ; Munugalavadla et al , ). With the development of novel isoform‐specific PI3K inhibitors, more selective targeting of the relevant isoforms has become possible, potentially permitting enhanced anti‐tumour activity and a reduction of off‐target effects.…”
mentioning
confidence: 94%